Fundraising Strategies for Private Madrasahs to Improve Service Quality: (Strategi Pendanaan bagi Madrasah Swasta untuk Meningkatkan Kualitas Layanan) - Misrawita; Hamdi Abdul Karim (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study discusses fundraising strategies in private madrasahs in response to limited government funding and increasing demands for quality education services. The study focuses on Islamic education management, with an emphasis on madrasah independence. The main question posed is: what strategies do private madrasahs employ in fundraising, and how do these strategies impact the quality of educational services? This study adopts a qualitative approach through case studies, with data collected from madrasah heads, committees, and the surrounding community. The results indicate that effective strategies include collaboration with committees, asset utilisation, alumni participation, and cultural approaches. These strategies significantly contribute to improving facilities, teacher welfare, and the quality of learning. This research emphasises the importance of participatory and innovative financial management in ensuring the sustainability of education in private madrasahs.